Conversor Boost bidirecional de alto ganho aplicado a um sistema fotovoltaico - Henn, Gustavo Alves de Lima (2008)
Aiming to overtake the issues caused by interconnecting photovoltaic panels to the conventional low voltage electric system, this work presents the analysis and the implementation of a high voltage gain boost converter connected to photovoltaic panels, and a bidirectional high voltage gain converter connected to a bank of batteries, which are used to store the excess of energy produced by the modules, and to supply the load when the panels cannot do it by themselves. A “perturb and observe” MPPT control algorithm for the high voltage gain boost converter was implemented to extract the maximum power from the photovoltaic panels. The control of the bidirectional converter is implemented in order to guarantee a 180 Vdc output voltage. This voltage level was chosen because it can be used to transform it in a 110 VRMS voltage by connecting the system to an inverter in the future. Besides, the algorithm control from both converters was implemented in a fully digital way. The main features of the proposed converters are: very simple switching control, low voltage stress levels on the switches, the presence of a magnetic coupling cell, which allows an even higher gain, and the magnetic components operating with the double of switching frequency. Theoretical analysis, design procedure, simulations and experimental results from a 500 W laboratory prototype are presented in order to validate the operation principle of the proposed system.